Russian in The 1740s. - Rosén, Thomas. (Academic Studies Press, 2022)
This investigation offers a broader perspective on the Russian language of the 1740s by analyzing sources that are seldom valued for their linguistic content. It shows that although literate Russians were exposed to a growing number of modern printed texts, they mostly kept to traditional forms of written language during this period.